A New Approach to Determine Gas Diffusion Coefficients in Porous Solids by EIS: Application for NH3 and CO2 Adsorption on Zirconia and Zeolite Type 5A. (4th October 2018) - Nguyen, Tien-Quang; Glorius, Maja; Breitkopf, Cornelia
Abstract : A new theoretical approach has been established to define transport coefficients of charge and mass transport in porous materials directly from impedance data; thus four transport coefficients could be determined. In case of ammonia adsorption on sulfated zirconia, the diffusion coefficient was figured out to be approximately the mobility diffusion coefficient of ammonium ions: 1.2 x 10 -7 cm 2 /s. The transport of carbon dioxide was examined for samples of zeolite type 5A in different hydration states. By impedance spectroscopy measurements, the diffusion coefficient of water vapor at 373 K is estimated to be about 7 x 10 -6 cm 2 /s. The influence of carbon dioxide adsorption on diffusion coefficients is studied based on two pellet types of zeolite 5A. The difference between polar and non-polar gas adsorption in porous solids is considered as changed characteristic of impedance.